ANALYSIS OF QUALITY OF ACTIVATED CARBON (Myristica fragrans) SHELL AS ADSORPTIVE AGENT - Hitijahubessy, Hendro (Universitas Pattimura, 2019)
The activated carbon made in this study is activated carbon in the form of powder and granules (a mixture of the two) by a chemical activation process using calcium oxide (CaO). The characterization of activated carbon refers to the Indonesian National Standard 06-3730-1995 concerning technical activated carbon with the indicators tested being moisture content, volatile matter content, total ash content, bound carbon content and iodine adsorption capacity. Based on research on the characterization of activated carbon, nutmeg shells have a moisture content of 0.6979 %, volatile matter content of 3.8781%, total ash content of 8.7323%, bound carbon content of 87.3896 % and iodine adsorption capacity of 325. 0694 mg/g. Iodine adsorption capacity aims to determine the adsorption capacity of activated carbon. Based on the technical quality standard of activated carbon regarding iodine adsorption capacity stipulated by SNI 06-3730-1995, researchers can explain that the pore capacity of nutmeg shell activated carbon is very good for use as an adsorbent. The important use of activated carbon in nutmeg shells as an adsorbent is expected to be utilized for water purification from bacteria, absorption of inorganic materials dissolved in water and cosmetic base ingredients.